Blooms of Alexandrium catenella in Coastal Waters of Chilean Patagonia: Is Subantarctic Surface Water Involved? - Crawford, David W.; Montero, Paulina; Daneri, Giovanni (Frontiers in Marine Science, 2021)
At the southern tip of South America, evidence of shellfish toxicity has been recorded in the accounts of early explorers and shipwreck survivors since the late 16th Century. Blooms of the toxic dinoflagellate Alexandrium catenella were described in the western Magellan Strait in the early 1970s and have since shown a northward progression through Chilean Patagonia, culminating in a catastrophic toxic event around Chiloé Island in 2016. This shift has taken place through coastal areas of extremely sparse human population density, and anthropogenically driven eutrophication is therefore unlikely to be significantly involved, at least in the south. However, human activities – such as salmon cultivation – may play a role in the intensification of blooms in the more densely populated areas of northern Patagonia. In the fjords and channels of Chilean Patagonia, phytoplankton assemblages are shaped by complex interactions between freshwater (FW) run-off and intrusions of subantarctic surface water (SASW). In the context of blooms of A. catenella, we review the properties of SASW – transformed in coastal waters into modified subantarctic water (MSAW). FW input is characterized by very low concentrations of dissolved inorganic nitrogen (DIN) and phosphorus (DIP), but relatively high concentrations of silicic acid (DSi); DIN and DIP are instead supplied predominantly by SASW which is severely deficient in DSi. These waters therefore show strong vertical gradients in DIN, DIP and DSi, but also potentially in dissolved trace metals and CO2. Large scale shifts in the relative inputs of SASW or FW can modify these vertical gradients, potentially forcing competitive changes in phytoplankton assemblages with latitude, with implications for growth and toxicity of A. catenella and other harmful species. The northward shift of blooms of A. catenella could be associated with anomalies in the Southern Annular Mode (SAM) that modify the influence of MSAW through variations in FW input to coastal waters. The historical presence of blooms in southern Patagonia and Tierra del Fuego, combined with the strongly contrasting conditions with latitude and depth, mean that southern Chile represents an ideal natural laboratory to study climatic and oceanographic influences on dynamics of A. catenella populations.